Diversity of endophytic actinomycetes in mandarin grown in northern Thailand, their phytohormone production potential and plant growth promoting activity - Arawan Shutsrirung (2018)
The rapid expansion of mandarin (Citrus reticulata L.) production areas with high agrochemical input in the highland areas of northern Thailand has resulted in negative effects in terms of production, environment, soil quality, and public health. The use of microorganisms as plant growth promoters is an alternative method to reduce agrochemical input. Thus, we studied the diversity of endophytic actinomycetes in mandarin and their potential as plant growth promoters. A total of 252 endophytic actinomycete isolates were recovered from mandarin. Based on spore chain morphology, cell wall type, and 16S rRNA gene sequence, the isolates were classified into six genera: Streptomyces, Nocardia, Nocardiopsis, Spirillospora, Microbispora and Micromonospora. The most frequent isolates recovered were members of Streptomyces (85.3%). Selected isolates (64 isolates) from these genera were evaluated for their indole-3-acetic acid (IAA) production potential in a medium with 2 mg mL-1tryptophan, and all the selected isolates showed the potential to produce IAA, with average values of IAA production of 13.34, 3.36, 140.38, 12.55, 1.40, and 6.19 μg IAA mL-1, respectively. Isolates of genus Nocardiopsis showed a very high ability to produce IAA that was the highest among all the genera, with values ranging from 62.23 to 222.75 μg mL-1. Twelve isolates selected from these genera were inoculated onto mandarin seedlings, and the results indicated that the shoot height, fresh shoot weight and fresh root weight of the seedlings were promoted by the inoculation of endophytic actinomycetes, with values ranging from 20.2 to 49.1%, 14.9 to 53.6%, and 1.6 to 102% over the control, respectively. © 2013 Copyright Japanese Society of Soil Science and Plant Nutrition.